Bruises of the mind: unmasking Gardner-Diamond syndrome in a middle-aged woman - Rathi, Ujjwal S.; Kharkar, Vidya; Joshi, Vijay D.; Bose, Agnikumar (International Journal of Research in Dermatology, 2025)
Psychogenic purpura, also known as Gardner-Diamond syndrome (GDS), is a rare psychocutaneous disorder characterized by the spontaneous development of painful, bruise-like skin lesions in response to emotional stress. Hereby reported is case of a middle aged-female, presenting with painful purpurae over bilateral lower limbs, with an underlying concealed history of stress. Further evaluation portrayed absence of any bleeding or clotting disorders, albeit with a positive auto erythrocyte sensitization test. Considering a diagnosis of psychogenic purpura, and after thorough psychological counselling, she depicted remarkable improvement in her skin lesions. This rare case report highlights the increased need for creating awareness amongst dermatologists about psychocutaneous diseases and emphasizes the importance of keen history taking, including an in-depth psychological evaluation. This report also underscores the role of autoerythrocyte sensitization test, making it an indispensable clinical tool in dermatological diagnosis, as every purpura does not reflect a coagulation disease or vasculitis.